A diversificação dos leiteiros da secção São Miguel: um estudo comparativo das rendas numa comunidade rural de Francisco Beltrão - PR entre os anos 2013 e 2018 - Poletto, Jéssica Ramos (2019)
Family farming plays a prominent role in the development of southwestern Paraná, especially considering its network of relations with cooperatives, agro-industries and trade in general, which boosts the local economy. This agriculture faces a growing process of modernization and technical and financial integration, which deepens as it gains access to a new form of credit. Therefore, this research aims to accompanya group of ten dairy families from the Community Section of São Miguel de Francisco Beltrão / PR for 5 years. The objective of this research was to follow the modernization trajectories of a group of farmers. and follow its historical evolution of capitals: human, physical, financial, social and natural. From this study, one can observe a trend of diversification of income sources, especially non-agricultural income and retirement, where only one family has only its agricultural income. It was also observed that most families modernized their agricultural equipment, making use of rural credit operations. Regarding the productive strategies, it was observed from families that diversified the agricultural income as cases of others that specialized the agricultural income. The issue that made the source of farm income more vulnerable was the health problem, and in one case the family closed all commercial farming activities and sold the farm equipment because of a health problem. Finally, the research also drewsome conclusions on the succession issue by noting that non-farm income opportunities are enabling young people in rural area.